Motor impulsivity differentiates between psychiatric inpatients with multiple versus single lifetime suicide attempts. (July 2017) - Colborn, Victoria A.; LaCroix, Jessica M.; Neely, Laura L.; Tucker, Jennifer; Perera, Kanchana; Daruwala, Samantha E.; Grammer, Geoffrey; Weaver, Jennifer; Ghahramanlou-Holloway, Marjan
Abstract: A history of multiple suicide attempts conveys greater risk for suicide than a single attempt. Impulsivity may partially explain the association between multiple attempts and increased risk. We examined trait impulsivity, ability to engage in goal-directed behaviors, and impulse control among psychiatrically hospitalized United States military personnel and their dependents. Individuals with a history of multiple versus single attempts had significantly higher motor impulsivity, indicating spur of the moment action. Providers are encouraged to directly assess and treat motor impulsivity among suicidal individuals. Further research should explore whether motor impulsivity is a mechanism of change in psychosocial suicide prevention interventions. Highlights: Impulsivity was examined in a sample of psychiatrically hospitalized military service members and beneficiaries. Groups were compared based on history of multiple vs. single suicide attempts. Individuals with multiple suicide attempts reported higher motor impulsivity. Providers should assess and target motor impulsivity in suicide prevention efforts.